Fine-needle aspiration biopsy of papillary thyroid carcinoma - Nasser, Selim M. (2000)
BACKGROUND Papillary thyroid carcinoma is the most common malignant neoplasm of the thyroid gland, and fine-needle aspiration biopsy (FNAB) often is the initial diagnostic method used in its detection. Prior studies have shown that immunohistochemical staining for various cytokeratins in general, and cytokeratin 19 (CK19) in particular, can be applied as an ancillary technique for diagnosing papillary thyroid carcinoma in histologic specimens. In the current study the authors assessed the diagnostic utility of CK19 to detect papillary carcinoma effectively in cytologic preparations of thyroid FNABs. METHODS Immunocytochemical staining with CK19 was performed on cytologic aspirates from 37 papillary thyroid carcinomas and 36 other lesions of the thyroid (14 follicular adenomas, 10 multinodular goiters, 5 cases of Hashimoto thyroiditis, 6 oncocytic [Hürthle cell] neoplasms, and 1 follicular carcinoma). All cases included in the study had a corresponding histopathology specimen. RESULTS Positive immunocytochemical reactivity for CK19 was identified in 34 of 37 papillary carcinomas and in 1 of 36 other thyroid lesions (sensitivity of 92% and specificity of 97%). Although the strongest reactivity was obtained in methanol fixed thin layer preparations, the antibody also was effective in detecting papillary carcinoma in alcohol fixed and air-dried smears. The single false-positive case was a follicular adenoma with focal areas of papillary hyperplasia. All other aspirates including those from cases of Hashimoto thyroiditis, multinodular goiter, follicular adenoma, oncocytic neoplasms, and follicular carcinoma were negative. CONCLUSIONS CK19 is an effective, highly sensitive, and specific ancillary tool for the diagnosis of papillary carcinoma in thyroid FNABs. Cancer (Cancer Cytopathol) 2000;90:307–11. © 2000 American Cancer Society.